UPF MAPS : plataforma de geolocalização para navegação no campus - Pereira Filho, Alisson Moreira (2025)
This work aims to develop a geolocation platform focused on navigation within the University of Passo Fundo campus. The proposal emerged from the need to improve spatial orientation and mobility for students and visitors in a large and decentralized physical structure. The system, called UPF Maps, allows users to locate buildings, academic areas, and points of interest, in addition to generating custom routes with search filters and information about accessibility and opening hours. Among the main results, the functionality for generating and sharing links and QR codes stands out. Validation will be conducted through technical and practical tests, including usability assessments based on a questionnaire. It is concluded that the proposed solution has the potential to improve communication between faculty and students, reduce navigation difficulties, and serve as a foundation for future integrations with the university’s institutional systems.